Somos da Quarta Colônia: os sentidos de uma identidade territorial em construção - Vendruscolo, Rafaela (2009)
This dissertation discusses the experience of nine counties in the central region of Rio Grande do Sul to form an inter-municipal consortium that resulted in the social construction of a new territory: the Fourth Colony. The study aimed to map the web of meanings that sustain the narrative about the territorial identity of the Fourth Colony, seeking also to see how this narrative is set in the identity negotiations and the gaze of visitors. The study is based on concepts that cover the contemporary identity issue nowadays, in a context permeated by large transformations in social relations and with the emergence of new identities. Combining analysis of the ethnographic research with other techniques as the analysis of discourse and content analysis of advertising materials as well as the use of structured questionnaires applied in events, it was found that the territorial identity of the Fourth Colony maintains itself under a web of meanings woven from a variety of elements. The natural and cultural heritage, customs, traditions, knowledge and practices of the old settlers are the references to belonging. The meanings of the identitary narrative are anchored, therefore, in the ethnic claim, principally Italian, referenced by a colonial past, a time constantly revisited and impassioned in the positive speeches, in the festive rituals and in other spaces of sociability. The narrative is based on myths of ancestry, having the gastronomy as an important matrix of identity and differentiation, producing constant requests for diffuse notion of belonging, with no pretensions to claim a uniqueness. Amid the negotiations set for the construction of local identity, it was found that the narrative uses a rhetoric of ethnic diversity, although extremely prevalent elements and meanings related to the Italian daily life and in the imagination of territoriality. It's known, therefore, that the construction of territorial identity of the Fourth Colony takes place in areas of interethnic friction, being immersed in power relations that maintain the narrative tied to a hegemonic order.